Etika sebagai Cabang Filsafat Aksiologi dan Relevansinya terhadap Profesionalisme Guru: Studi Literatur - Vickri Syakara, Vanesya; Fiana Putri, Isfaul; Taufiq, Ahmad (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
The increasing complexity of moral challenges faced by teachers, including violations of professional ethics, misuse of social media, and ethical dilemmas in educational practice, highlights the importance of ethics as the moral foundation of the teaching profession. This study aims to analyze ethics as a branch of axiological philosophy and examine its relevance to strengthening teacher professionalism. This research employed a qualitative approach using a literature study method. The study analyzed from scholarly references, consisting of books, national and international journal articles, and official documents published between 2020 and 2026. The literature was selected based on relevance, credibility, accessibility of full-text publications, and topical suitability. Data were analyzed using content analysis and a descriptive-critical approach through data reduction, data presentation, interpretation, and conclusion drawing. The findings indicate that ethics constitutes one of the principal branches of axiology, focusing on values, moral responsibility, goodness, and propriety in human actions. Within the educational context, ethics serves as a normative foundation that guides teachers in making responsible professional decisions. Furthermore, ethics significantly contributes to strengthening teachers’ integrity, honesty, accountability, moral commitment, and exemplary conduct as essential characteristics of professional educators. Therefore, this study recommends integrating ethical and philosophical education more systematically into teacher education programs and continuous professional development to enhance teacher professionalism and promote humane, dignified, and character-oriented education.